DIFFERENTIAL SCANNING CALORIMETRY (DSC) AN ESSENTIAL AND CRITICAL INSTRUMENT IN OPTIMIZING LYOPHILIZATION PROCESS: Pharmaceutical Science-Pharmaceutics - PATRA, MAUNAB; KUMAR ACHARYA, PRAJIT; SETH, SAURABH; SHADANGI, MEENAKSHI (International Journal of Life Science and Pharma Research, 2013)
At present, lyophilization has become an important in-course process which has been proved to increase the stability of a parenteral product which causes a consequent increase in its bioavailability. A thorough understanding of a formulation provides the basis for developing the freeze-drying cycle parameters, such as freezing temperature, annealing temperature, shelf temperature, vacuum level, and time duration. The steps of lyophilization have three distinctive parts which is to be done with utmost care to restrict the drug products from degrading. Some characterization has to be done to reach a conclusion whether the drug product is as same as was before lyophilization i.e. the drug did not undergo any kind of degradation. Differential scanning calorimetry (DSC) is an experimental technique for measuring the energy necessary to establish a nearly-zero temperature difference between sample and reference. The present review article demonstrates a vivid description of the reason of extreme usefulness of DSC and its modifications for examining the Tg (Glass temperature) properties of freeze-dried pharmaceutical systems